PENGARUH ARUS KAS BEBAS, COLLATERALIZABLE ASSETS, DAN KEBIJAKAN UTANG TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Muhammad Arfan; Trilas Maywindlan (Jurnal Telaah dan Riset Akuntansi, 2013)
The aim of this study is to investigate the effect of free cash flow, collateralizable assets, and debt policy, both simultaneously and partially, to dividend policy on listed companies at Jakarta Islamic Index for the year 2007-2010. The study type used is verificative study or hypothesis testing study. By using census method and unbalanced panel data, there are 91 firm observations fulfilling the population criteria.The source of data is secondary data obtained from the capital  market reference centre at the Indonesia Stock Exchange. The multiple regression analysis model is used to test the hypothesis.The results show that (1) free cash flow, collateralizable assets, and debt policy simultaneously have influence to dividend policy (2) free cash flow has positive influence to dividend policy (3) collateralizable assets has positive influence to dividend policy, and (4) debt policy has negative influence to dividend policy.Keywords:  free cash flow, collateralizable assets, debt policy, dividend policy